Evaluating association between thrombocytopenia and hypertension in pregnancy and its fetomaternal outcome - Alisha Gupta,; Vandana Dhama,; Shakun Singh,; Rachna Chaudhary, (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Hypertension in pregnancy is common complication of pregnancy with incidence 5-15% and associated with maternal and perinatal mortality and morbidity. Platelet count is most simple, rapid and economical method of prediction of pregnancy induced hypertension. The aim and objective of study was to corelate with severity of thrombocytopenia and its association with fetal and maternal outcome. Methods: This study was a case control study and was conducted in department of obsterics and gynecology, SVBP hospital attached to LLRM medical college, Meerut, from October 2020 To June 2022. Total number of 100 pregnant females out of which 50 pregnant females with hypertension as cases and 50 pregnant females without hypertension as control were included in study. Observations were tabulated, analysed and conclusions were drawn. Results: Out of 50 cases 43 patients developed preeclampsia thus giving incidence of 43 % and out of which 21 patients had mild thrombocytopenia,13 moderate thrombocytopenia and 4 severe thrombocytopenia. The mean age amongst cases was 26.73±5.19SD and the mean age amongst control was 28.09±4.83. There was very high significant relationship between the degree of thrombocytopenia with severity of hypertension during pregnancy (at p <0.01). 24% fetuses had preterm birth, 8% had fetal growth restriction, 2% were IUD and 2% mortality. 2% of mothers had DIC,8% had post-partum hemorrhage, 6% had abruption ,4% had pulmonary edema and 6% mortality. Conclusions: Thrombocytopenia is most common and can be life threatening complication of pregnancy induced hypertension. Therefore, platelet count can be used as an early, easy, simple, most economical and rapid test to assess severity of preeclampsia and to prevent its progression to eclampsia, HELLP syndrome and DIC.